Information processing in cells and tissues : 10th International Conference, IPCAT 2015, San Diego, CA, USA, September 14-16, 2015, Proceedings /: 10th International Conference, IPCAT 2015, San Diego, CA, USA, September 14-16, 2015, Proceedings. (2015) - Unknown
No abstract available